2021
DOI: 10.3389/fevo.2021.626752
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating DNA Barcoding for Species Identification and Discovery in European Gracillariid Moths

Abstract: Gracillariidae is the most species-rich leaf-mining moth family with over 2,000 described species worldwide. In Europe, there are 263 valid named species recognized, many of which are difficult to identify using morphology only. Here we explore the use of DNA barcodes as a tool for identification and species discovery in European gracillariids. We present a barcode library including 6,791 COI sequences representing 242 of the 263 (92%) resident species. Our results indicate high congruence between morphology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 75 publications
0
40
0
1
Order By: Relevance
“…The remaining 5-10% will need even more detailed population-level studies to uncover haplotype networks of complex species relations, as demonstrated for birds [104]. As such, results on DNA barcoding of Sciaroidea from the Nordic region are in line with great success rates reported after a rigorous revision for several other, better-studied taxa, such as gracillariid moths [105,106].…”
Section: There Is Hope For You Yet Taxonomymentioning
confidence: 76%
“…The remaining 5-10% will need even more detailed population-level studies to uncover haplotype networks of complex species relations, as demonstrated for birds [104]. As such, results on DNA barcoding of Sciaroidea from the Nordic region are in line with great success rates reported after a rigorous revision for several other, better-studied taxa, such as gracillariid moths [105,106].…”
Section: There Is Hope For You Yet Taxonomymentioning
confidence: 76%
“…On the basis of the forewing pattern and genitalia we follow Z. Laštůvka (in Lopez-Vaamonde et al 2021) who regards this as Phyllonorycter ochreojunctella, a species not considered by Varenne & Nel (2015), and we hereby introduce the synonymy.…”
Section: Phyllonorycter Acericorsica Varenne and Nel 2015mentioning
confidence: 99%
“…However, the majority of Hyperlais have not been barcoded so far. Leraut (2012) discussed an eventual conspecitify with H. dulcinalis (Treitschke, 1835) and H. glyceralis (Staudinger, 1859) with subspecific status, but both species lack DNA barcodes.…”
Section: Hyperlais Rosseti Varenne 2009mentioning
confidence: 99%
“…We expected to find archival leaf mines in herbaria specimens in Eastern Asia well before the beginning of the invasion and in Western Europe only after the invasion event. We also took advantage of the recent advances in DNA barcoding of samples with degraded DNA 22,23 to analyse larvae and pupae found inside archival leaf mines to understand the genetics of invasion and explain the high level of haplotype diversity in the neocolonized area in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…(Malvaceae) in the Palearctic. In the last few decades, this species, which was originally known from East Asia (Japan, Korea, Russian Far East) 14,15,16,17 , invaded Western Palearctic and became a pest of lime trees 18,19,20,21,22 . In a recent analysis of COI mtDNA barcodes of 377 P. issikii's specimens collected across the modern rage in the Palearctic, we revealed unusually high genetic diversity of the species in the recently invaded region (Western Palearctic) compared to the putative native region (Eastern Palearctic, in particular Eastern Asia) questioning the hypotheses about the moth's region of origin and geographic expansion 20 .…”
Section: Introductionmentioning
confidence: 99%